Selective localization of starch nanocrystals in the biodegradable nanocomposites probed by crystallization temperatures. (1st January 2020) - Zhang, Guorui; Xie, Wenyuan; Wu, Defeng
Graphical abstract: Highlights: Starch nanocrystals filled immiscible PHB/PBS blend composites are prepared. Starch nanocrystals were dispersed in PHB phase and on PHB/PBS interfaces. Change of crystallization temperatures is a probe to detect selective localization. Phase structure can be regulated by selective localization of starch nanocrystals. Abstract: Starch nanocrystal (SNC), was used as the third component to prepare nanocomposites with biodegradable poly( β -hydroxybutyrate)/poly(butylene succinate) (PHB/PBS) blend. The results reveal that SNC shows strong nucleation to the two matrix polymers. However, the crystallization temperature of PHB is highly dependent on the SNC loadings, whereas that of PBS not. This is because SNCs have preferential localization in the immiscible matrix polymers: mainly dispersed in the continuous PHB phase and on PHB/PBS phase interfaces. Therefore, alteration trend of crystallization temperatures can be used as good probe to evaluate selective localization of SNCs in the immiscible blends containing two semicrystalline polymers. The nucleation activities of SNCs, and their interaction energy densities in the two polyesters, as well as the tensile behaviors of ternary nanocomposites, were then detected, aiming at establishing a simple route to prepare green nanocomposites with tailorable multi-phase morphology and balanced mechanical properties using starch and biodegradable aliphatic polyester blends.